The Ponte Delle Chianche on the Via Traiana in Buonalbergo (Benevento, Italy): New Data for an Integrated Study - Ivan Ferrari (Heritage)
This article illustrates a systematic and updated study of the Ponte delle Chianche, a Roman bridge on the ancient Via Traiana built at the beginning of the second century AD and located near Buonalbergo (Benevento, Italy). The study aimed to retrieve all information contained in literary sources and to cross-reference them with new data from research conducted in recent years. Thanks to an instrumental metric survey of the structures, both the construction techniques used and the bridge construction process were better understood, elements that were then incorporated into the development of a 3D reconstruction proposal. At the same time, a close visual analysis of the structures led to the discovery of a large number of brick stamps, also unpublished, which is important for understanding the logistical aspects of the building materials. The results obtained will be used to implement a comprehensive project for the recovery and securing of the property.